The Implementation of The Death Penalty Execution After A Final Verdict In Indonesia: Analysis of Supreme Court Decision No. 2 K/Pid. Sus/2007 - Danny, Aditya Prima (Sinergi International Journal of Law, 2023)
In the realm of public knowledge, capital punishment is recognized as a severe and, at times, inhumane form of criminal punishment. This implies that individuals tend to be hesitant when faced with the impending reality of their own death, understanding that the ultimate decision lies in the hands of a higher authority. Consequently, individuals should be conditioned to become accustomed to the idea of witnessing and possibly experiencing the brutality, cruelty, and injustice associated with capital punishment. While these elements may instill fear, it is important to recognize that the death penalty holds an equal standing with other punitive laws. Its purpose lies in achieving national peace, security, and societal well-being.